Therapeutic Relational Communication and Resilience among Nursing Professionals in a Pandemic Situation - Isabel Mª Sáez-Ruiz; Verónica V. Márquez-Hernández; Genoveva Granados-Gámez; Anabel Corral-Granados; Consuelo Artero-López; Lorena Gutiérrez-Puertas (MDPI AG, 2024)
Therapeutic relational communication has become a fundamental human resource in the nursing profession. The positive relationship between nurse-patient communication and resilience has been shown in several studies. However, these aspects can be affected in adverse circumstances. The purpose of this study was to identify the relationship between nurse-patient therapeutic relational communication and the resilience of nursing professionals in adverse circumstances. A cross-sectional study with a sample of 201 nursing professionals was conducted. This study found high levels of both therapeutic relational communication between nurses and patients as well as resilience among nurses. The sociodemographic variables of age and years of experience in the profession positively correlated with the data obtained through the measurement instruments. The co-relational analysis revealed a positive correlation between nurse-patient therapeutic relational communication and nurse resilience, and the regression analysis showed that levels of successful therapeutic communication skills were minimally explained by resilience. Nursing professionals who participated in this study demonstrated adequate levels of therapeutic relational communication with their patients as well as adequate levels of resilience required to cope with the challenges of the COVID-19 pandemic in their daily nursing practice. This study was not registered.